Yield attributes of rice (Oryza sativa) under acidic, low-phosphorus and high-iron soils of north-eastern region of India - SHARMA, B D; HORE, D K (The Indian Journal of Agricultural Sciences, 2013)
In a path analysis and correlations study of 50 diverse varieties of rice (Oryza saliva L.) in randomized block design experiment conducted on acidic, P-deficient and high-iron soils under lowland conditions of mid-hills of Meghalaya, panicle weight was found the most reliable single yield component. Besides, panicle length, panicles/plant and days to flower were the factors that deserve priority for selection of well-adapted superior types.